Kualitas Atraksi Wisata Pasar Terapung Banjarmasin Terhadap Kepuasan Wisatawan - Afrilia Elizabet Sagala; Afrilia Elizabet Sagala (Kepariwisataan: Jurnal Ilmiah, 2023)
Floating markets are markets that are located and all activities are carried out on water and are found in areas that have many large rivers or tributaries and lakes where residents or local people carry out many of their daily activities or activities on water. The development of river-based tourism with the Floating Market as its main icon will have a major impact on the City of Banjarmasin if it is developed in a planned, integrated and comprehensive manner. This research is qualitative with a descriptive exploratory approach. Data was collected through in-depth interviews, direct observation, Focus Group Discussion (FGD) and literature study. Research informants consisted of Pokdarwis tourism actors, groups of Floating Market traders as input materials in preparing research reports. Field data and findings were further analyzed using SWOT Analysis. The results of the research need for public awareness and collaboration between sectors to revive the Muara Kuin floating market as a destination that can compete with other artificial destinations in the city of Banjarmasin. The involvement of the government, especially the tourism agency, is expected to be able to organize the management of attractions so that they are of high quality and the tourists who come are satisfied to visit. Tourist satisfaction can be measured through length of stay and purchasing power when visiting a destination. Lack of supporting facilities, as well as "entertainment" enjoyed by tourists through icons, events and local guides that help tourists travel, raise awareness with human resource training/certification, especially tourism actors as local guides, providing dock spot icons that can provide awareness for tourists, development of supporting facilities in the form of: TIC, clean toilets, home stay, repair of riverside house facades to change the impression of slums